Kepemimpinan Kepala Sekolah Efektif (Perspektif Pendidikan Islam) - Azhar, Sopiah (Inspiratif Pendidikan, 2016)
In UU No 20/2 003 (regulation number 2 0/2003) about national education system, it has been mentioned that national education is aimed to improve potentials of learner to be faithful person and to be democratic, responsible civilian. In the context of Islamic education, it needs to be run maximally by emphasizing religious value. Vision and mission need to be determined and religious lesson is used as a base in determining vision and mission of the institution. The use of principle of fastabiqul khairat becomes a value needed to create vision and mission determined, institution manager in must give an example to the staff by having good characteristic such as: sincere, honest, fair, responsible, dynamic, practical and flexible. Effective and responsible head master is a person who can lead the education institution.